O uso de uma ferramenta para avaliação e monitoramento da fragilidade em idosos, segundo a percepção de profissionais da atenção primária: desafios e benefícios - Generoso, Fernanda Karoline (2020)
Since the 1960s, the Brazilian population has been experiencing a rapid process of aging, the frail elderly person is considered a priority for public health policies, it demands care, family and social support. The aim of the present study was to identify the relationship between sociodemographic variables, health perception and social support with frailty in the elderly registered in the FHU and identify the perception of team members about a tool that assesses fragility. This is a study of method mixed, carried out in a city in the interior of São Paulo. The population consisted of seven community health agents and a health professional from three Health Units in the Family and results of evaluations of the elderly who make up the research database the largest to which this study was linked. The study used analytical procedures to examine relationships between variables related to frailty and health condition of the elderly and conducted data collection through semi-structured interviews, focus groups and analyzes documentary in medical records. All ethical procedures were respected. The results evaluated by means of Fried's frailty assessment indicated associations between age and frailty and negative correlation between frailty and assessed social support by the MOS instrument. The findings also demonstrate that assessments are not used for health professionals to identify frailty, but reports it was possible to identify the effectiveness of the computational tool and the importance of using of technologies in primary health care.